Efficiency of Islamic banks in selected member countries of the Organisation of Islamic conference - Dewi, Meranti Kartika; Sulaiman, Maliah; Ferdian, Ilham Reza (Inderscience Enterprises Ltd, 2010)
This study aims to investigate the relative efficiency amongst Islamic banks in selected OIC member countries from 2002 to 2006, by observing performance of 25 Islamic banks in 14 countries. It employs DEA method by using intermediation approach. Additionally, regression is used to find the correlation between efficiency scores and some of the performance indicators. The result shows that during 2002-2006, Islamic banks in the OIC-LDCs were the most efficient ones. Lastly, efficiency level of Islamic banks in the study was significantly and positively influenced by ETAR, ROA, and LDR. In contrast, efficiency score is negatively related to OEOI.